Iranian postmenopausal women’s perspectives on sexual satisfaction: A qualitative study - Nasim Shahrahmani; Raheleh Babazadeh; Abbas Ebadi (PLoS ONE, 2025)
Sexual satisfaction is a key component of human sexuality and is often considered the final stage of the sexual response cycle. Menopause is a physiological phenomenon characterized by various physical, mental, and sexual changes. This qualitative study aimed to explain the concept of sexual satisfaction from the perspective of Iranian postmenopausal women. the study involved 22 married postmenopausal women aged 40–70 years conducted from April 8, 2023, to March 4, 2024, at health centers affiliated with Kerman University of Medical Sciences. Participants were selected through purposive sampling to maximize diversity. Data were collected via semi-structured interviews until saturation was reached and were analyzed following the Graneheim and Lundman method using MAXQDA software. The study identified 16 subcategories and seven main categories include: 1. Sociocultural and religious factors, 2. Individual and contextual characteristics, 3. Psychological factors, 4. Traces of dysfunctional married life, 5. Sexual satisfaction following positive sexual interactions, 6. Sexual helplessness in menopause, 7. Sexual values in menopause. Sexual satisfaction during menopause is a mental, dynamic, and interactive concept significantly influenced by an individual’s perception of their sexual relationship experiences and marital life. Physiological changes during menopause can lead to feelings of sexual helplessness, which impacts sexual satisfaction. Postmenopausal women may find that intimacy and emotional closeness with a sexual partner have a more substantial effect on sexual satisfaction than physical acts. Healthcare providers should develop interventions tailored to the sexual health needs of postmenopausal women, considering cultural, psychological, and physiological factors. Additionally, enhancing access to sexual health education can empower these women to articulate their needs and improve their sexual satisfaction.